Komunikasi Interpersonal Atasan-Bawahan dan Iklim Komunikasi Organisasi terhadap Kinerja Pegawai Generasi Z pada Kantor Pelayanan Pajak Pratama Bangko - Arie Erlangga; Ernita Arif; Asmawi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to investigate the influence of manager-employee interpersonal communication and organizational communication climate on the performance of Generation Z employees at the Bangko Pratama Tax Office. The census technique was utilized involving the entire population of Generation Z employees at the Bangko Pratama Tax Office as respondents. Multiple linear regression analysis was employed to analyze data obtained from 53 respondents. The research findings indicate a positive and significant influence between manager-employee interpersonal communication and organizational communication climate with the performance of Generation Z employees at the Bangko Pratama Tax Office. The regression coefficient value for manager-employee interpersonal communication is 0.487, and for organizational communication climate is 0.378. Statistical tests also demonstrate that collectively, manager-employee interpersonal communication and organizational communication climate have a significant impact on the performance of Generation Z employees. Enhancements in manager-employee interpersonal communication and organizational communication climate would enhance the performance of Generation Z employees. Overall, 78.1% of the variance in the performance of Generation Z employees can be explained by manager-employee interpersonal communication and organizational communication climate, while the remaining 21.9% is explained by other unanalyzed variables in this study